Antitumor effect of bromo-naphthoquinone associated with tannic acid in triple negative breast cancer cells - Carvalho, Emanuelle Pangoni de; Pessoa, Adriano de Souza; Iano, Flávia Godoy [UNESP]; Ribeiro, Laura; Leme, Bianca; Borges, Luis Francisco; Sanches, Mariana Liessa Rovis; Ximenes, Valdecir Farias [UNESP]; Oliveira, Rodrigo Cardoso de (Elsevier, 2024)
Triple-negative breast cancer (TNBC) is an aggressive type of tumor that tends to recur in women. It is characterized by the absence of hormonal receptors, making it challenging to diagnosis and treatment. In this study, we investigated the anti-tumor effects of a pro-oxidant naphthoquinone derivative called bromo-naphthoquinone (BrNQ) isolated and combined with the antioxidant tannic acid (TA) in order to improve treatment. We used tumor cell lines MDA-MB-231 and HCC-70, as well as normal breast cells, HB4a, as control. Initially, viability assays conducted within 72 hours showed that the combination of compounds had a synergistic and notable cytotoxic effect on the tumor cells. The increased cytotoxicity appeared to be linked to changes in the cellular redox status, as indicated by a significant rise in reactive oxygen species (ROS) and though alterations in the level of thiol. The treatment also induced apoptosis, inhibited proliferation, and reduced migration, particularly in the MDA-MB-231 cell line. Furthermore, relevant changes were detected in the expression of Bcl-2, BAX, FAS, and BIRC-5, while no significant alteration in the expression of NOXs was observed. In conclusion, our findings suggested that the combination of BrNQ and TA though the ability to change redox status in tumor cells could act as a potential adjuvant treatment modality for improve prognosis in TNBC.
Keywords: Bromo-naphthoquinone; Reactive oxygen species; Tannic acid; Triple-negative breast cancer